The book of Joe - Tropper, Jonathan (Random House Inc., 2004)
Joe Goffman was fifteen years out from his sleepy home town when he wrote Bush Falls, a searing critique of its people and institutions. The book was a runaway bestseller, and led to an even more successful movie. Now, however, Joe's got a problem. His father has suffered a stroke, and that means that Joe has to go back to his birthplace after having successfully antagonized every person living there. Can Joe survive the reservoirs of hatred that have been waiting to pour down upon him? Just maybe